Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine